Yellow Brazilian Pepper-tree Leaf Galler (suggested common name) Calophya latiforceps Burckhardt (Insecta: Hemiptera: Calophyidae: Calophyinae) - James P. Cuda; Patricia Prade; Carey R. Minteer-Killian (EDIS, 2017)
In the late 1970s, Brazilian peppertree, Schinus terebinthifolia Raddi (Sapindales: Anacardiaceae), was targeted for classical biological control in Florida because its invasive properties (see Host Plants) are consistent with escape from natural enemies (Williams 1954), and there are no native Schinus spp. in North America. The lack of native close relatives should minimize the risk of damage to non-target plants from introduced biological control agents (Pemberton 2000). [...]